IMPLEMENTASI PEMBELAJARAN MIKROBIOLOGI DAN PARASITOLOGI PADA MATERI VIRUS TERHADAP HASIL BELAJAR MAHASISWA APIKES IRIS PADANG (Jurnal Bioconcetta, 2019)
This research started from the problem of low student results on the material of the virus. It is evident in the quiz grades of students who are under the minimum competence criteria (KKM) so that the value of courses on microbiology and parasitology virus material is not appropriate Â as expected. This research purpose to know the implementation learning of microbiology and parasitology at the material Virus in the Apikes Iris Padang which includes the design, implementation and assessment of learning. Informants research is lecture of Microbiology and Parasitology and Students Apikes Iris Padang. This type of research is descriptive research with a qualitative approach. Based on the findings, we can conclude that (1) Lecturers are not planning independently contextual learning context-sensitive places or classrooms where learning implementation. (2) Lecturer implementing the learning has not been effective and efficient due to: (a) lecturers have not been able to utilize time effectively, (b) lecturers have not been able to establish and selecting instructional media appropriate in accordance with the criteria of the study material (c) the learning has not been effective due to the limited number and quality of laboratory equipment. (3) Lecturer already conducted an assessment of student learning outcomes for the quiz with the mechanisms and procedures that have not been right.This research started from the problem of low student results on the material of the virus. It is evident in the quiz grades of students who are under the minimum competence criteria (KKM) so that the value of courses on microbiology and parasitology virus material is not appropriate Â as expected. This research purpose to know the implementation learning of microbiology and parasitology at the material Virus in the Apikes Iris Padang which includes the design, implementation and assessment of learning. Informants research is lecture of Microbiology and Parasitology and Students Apikes Iris Padang. This type of research is descriptive research with a qualitative approach. Based on the findings, we can conclude that (1) Lecturers are not planning independently contextual learning context-sensitive places or classrooms where learning implementation. (2) Lecturer implementing the learning has not been effective and efficient due to: (a) lecturers have not been able to utilize time effectively, (b) lecturers have not been able to establish and selecting instructional media appropriate in accordance with the criteria of the study material (c) the learning has not been effective due to the limited number and quality of laboratory equipment. (3) Lecturer already conducted an assessment of student learning outcomes for the quiz with the mechanisms and procedures that have not been right.